2016
DOI: 10.1177/1352458516666186
|View full text |Cite
|
Sign up to set email alerts
|

Novel fMRI working memory paradigm accurately detects cognitive impairment in multiple sclerosis

Abstract: Background Cognitive impairment (CI) cannot be diagnosed by MRI. Functional MRI (fMRI) paradigms such as the immediate/delayed memory task (I/DMT), detect varying degrees of working memory. Preliminary findings using I/DMT, showed differences in Blood Oxygenation Level Dependent (BOLD) activation between impaired (MSCI, n=12) and non-impaired (MSNI, n=9) MS patients. Objectives To confirm CI detection based on I/DMT’ BOLD activation in a larger cohort of MS patients. The role of T2 lesion volume (LV) and EDS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Finally, we would like to highlight advances of fMRI and cognitive research in MS [78], although there has been some controversies about the real meaning of fMRI results, it seems that early changes can be seen, even in cognitively preserved patients, including higher recruitment of non-related areas, such as supplementary motor cortex during working memory tasks [113] or by changes in activity properties of regions highly related to cognitive functions, as centrality measures of the default mode network [114], changes that may be used as a biomarker for neurocognitive rehabilitation [115] especially, resting state fMRI [116,117,118].…”
Section: Neural Basis Of Cognitive Impairment In Msmentioning
confidence: 99%
“…Finally, we would like to highlight advances of fMRI and cognitive research in MS [78], although there has been some controversies about the real meaning of fMRI results, it seems that early changes can be seen, even in cognitively preserved patients, including higher recruitment of non-related areas, such as supplementary motor cortex during working memory tasks [113] or by changes in activity properties of regions highly related to cognitive functions, as centrality measures of the default mode network [114], changes that may be used as a biomarker for neurocognitive rehabilitation [115] especially, resting state fMRI [116,117,118].…”
Section: Neural Basis Of Cognitive Impairment In Msmentioning
confidence: 99%
“…Several previous studies have shown reorganization of the brain in patients with MS across systems, with an emphasis on the motor (Zeller & Classen, ), visual (Toosy et al ., ; Korsholm et al ., ; Jenkins et al ., ; Gallo et al ., ) and cognitive (Helekar et al ., ; Hulst et al ., ; Nelson et al ., ) domains. Reorganization within the motor system in the remitting phase of MS has mostly been demonstrated by means of functional magnetic resonance imaging (fMRI).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent fMRI study (Nelson et al, 2017), reduced activation of prefrontal cortex was observed in cognitively impaired MS patients on a working memory task compared to MS patients who were cognitively intact.…”
Section: Neuroimagingmentioning
confidence: 91%